Life‐history evolution in the anthropocene: effects of increasing nutrients on traits and trade‐offs. (13th June 2015) - Snell‐Rood, Emilie; Cothran, Rickey; Espeset, Anne; Jeyasingh, Punidan; Hobbie, Sarah; Morehouse, Nathan I.
Abstract Variation in life‐history traits can have major impacts on the ecological and evolutionary responses of populations to environmental change. Life‐history variation often results from trade‐offs that arise because individuals have a limited pool of resources to allocate among traits. However, human activities are increasing the availability of many once‐limited resources, such as nitrogen and phosphorus, with potentially major implications for the expression and evolution of life‐history trade‐offs. In this review, we synthesize contemporary life history and sexual selection literature with current research on ecosystem nutrient cycling to highlight novel opportunities presented by anthropogenic environmental change for investigating life‐history trait development and evolution. Specifically, we review four areas where nutrition plays a pivotal role in life‐history evolution and explore possible implications in the face of rapid, human‐induced change in nutrient availability. For example, increases in the availability of nutrients may relax historical life‐history trade‐offs and reduce the honesty of signaling systems. We argue that ecosystems experiencing anthropogenic nutrient inputs present a powerful yet underexplored arena for testing novel and longstanding questions in organismal life‐history evolution.